The Informational Foundations of Organization in Physical and Biological Systems : Toward an Extended Thermodynamic Principle of Self-Organization - Barack Ndenga (Publisher, 2025)
Understanding how organized structures emerge and persist in physical and biological systems remains one of the central challenges of modern science. While classical thermodynamics successfully describes energy conservation and entropy production, it does not explicitly account for the role of information in driving organization, stability, and structure formation. In this article, I propose a unifying theoretical framework in which information is treated as a fundamental physical quantity governing organization in complex systems. I introduce the concept of organizational efficiency, a measure capturing the balance between usable information and effective entropy, and argue that this balance determines the capacity of a system to self-organize. I demonstrate how this informational perspective naturally extends thermodynamic reasoning beyond equilibrium and provides a common language for phenomena observed in physics, biology, and artificial systems.The framework offers new insights into self-organization, robustness, and the emergence of structured behavior, and establishes conceptual foundations for an extended thermodynamic principle centered on information.
This publication introduces a unified theoretical framework for understanding organization in physical and biological systems through the lens of information. The work argues that information plays a central role in shaping structure, stability, and self-organization, extending classical thermodynamic perspectives. By framing organization as the result of an information–entropy balance, the article provides conceptual foundations applicable to non-equilibrium physics, living systems, and adaptive processes.The study aims to bridge thermodynamics, information theory, and complexity science, offering new insights into the emergence and persistence of organized behavior across natural systems.